The Salamancas. Ethnographic Accounts, Oral History and Collective Memory (Anclajes, 2020)
The main aim of this work is to identify a narrative space in which two different traditions come together, the Hispanic legitimized one and the original  peoples’  subordinated  to  colonial  practices.  From  the  study  of  the  Salamanca subject matter, we propose to go deeply into the recollections and  the  collective  memory  of  the  symbolic  processes  that  tend  to  become  invisible by the cultural hegemony of European origin. The analysed corpus is made up of Tehuelche testimonies compiled in the 60s by linguist Jorge Suárez and unpublished until 2006 (Fernández Garay y Hernández), and some oral texts recorded among internal migrants of the Argentine Patagonia and Chile in the context of “Workshops of History and Memory,” during an adults’ lit-eracy course, in which most participants proclaimed themselves as mapuches. (Bahía Blanca, Buenos Aires Province, 1995-2012).
Keywords: Salamanca; Ethnography; oral history; native peoples; collective memory